Perineural Invasion as a Prognostic Factor in Laryngeal Squamous Cell Cancer: A Matched-Pair Survival Analysis. (21st October 2021) - Zhu, Xiaoli; Duan, Fei; Zhu, Yingying; Shi, Xiaohua; Sun, Shuai; Cheng, Yuejuan; Chen, Xingming
Abstract: Background: The purpose of this study was to compare survival outcomes in patients with perineural invasion (PNI)-positive laryngeal squamous cell carcinoma (LSCC) and patients with PNI-negative LSCC. Methods: A total of 1, 272 patients with LSCC, diagnosed between 2008 and 2017, were included in this study. LSCC Patients with and without PNI were matched based on possible confounding factors. Survival analysis was performed using Kaplan–Meier estimates and the Cox proportional hazards model. Results: Of the 1, 272 LSCC patients, 118 (9.28%) were positive for PNI. Compared to PNI-negative patients, PNI-positive LSCC patients had significantly worse overall survival (OS) ( p  = 0.017), disease-specific survival (DSS) ( p  = 0.034) and recurrence-free survival (RFS) ( p  = 0.002). After pair matching, cohorts consisted of 118 patients in the PNI-positive group and 118 in the PNI-negative group. Significantly increased risk of OS (HR, 2.17; 95% confidence interval [CI], 1.29–3.61, p  = 0.003), DSS (HR, 2.07; 95% CI, 1.32–3.24, p  = 0.004) and RFS (HR, 2.65; 95% CI, 1.59–4.40, p  < 0.001) was observed after adjustment for prognostic variables. Conclusions: Patients with PNI-positive LSCC have significantly worse survival outcomes compared to patients with PNI-negative LSCC.